Relationship between BMI and Dental caries index in preschool children in Babol - Maryam Ghasempour; Karimollah Hajian; Zoleikha Moazzezi; Maryam Zovvar (Isfahan University of Medical Sciences, 2011)
Introduction: Advanced untreated dental caries can cause pain and discomfort and influence nutrition and growth in children. The aim of this study was to evaluate dental caries status (dft) and body mass index (BMI) and their relationship in preschool children in Babol. Materials and Methods: This descriptive-analytical, cross-sectional study was carried out on 600 healthy preschool children aged 3‒6 years in kindergartens of Babol. After measuring weight with a standard weighing machine (SECA) and height with a standard graduated ruler, BMI was calculated and entered in the curve of standards to determine percentages. In addition, dft was determined according to WHO criteria. Children with known systemic diseases were excluded from the study. Data was analyzed by qui-squared test and ANOVA.Results: Of 600 children, 206 (34.3%) children were caries-free. Regarding BMI percentages, 62% of children were normal, 15.3% were overweight and at risk of being overweight, and 22.7% were underweight. The relationship between mean of BMI according to d and f was not significant but there was an increase in dental caries with an increase in body weight (p value = 0.002); however, there was no significant relationship between weight and the number of fillings (p value = 0.08). Conclusion: Under the limitations of this study, the least and highest number of decay processes and fillings were found in "underweight" and "at risk of overweight" children, respectively. There was a significant increase in caries rate with an increase in the mean of body weight. Key words: BMI, Index, Dental caries, Children, Preschool